Design of 'minimum energy' culvert sections - Ratnor Saliman Rabu (2009)
A culvert is a simple structure, often a pipe, projecting through an embankment to allow runoff to move from an upstream to a downstream area. A culvert section consists of an entrance, an exit and a barrel connecting the two. Unlike bridges, they are usually designed to operate with the inlet submerged if conditions permit. This allows for a hydraulic advantage by increased discharge capacity. Despite its simple structure, the hydraulics of a culvert can be quite complex. The culvert may or may not be full; the exit may or may not be submerged. The flow regime may follow subcritical or supercritical form, and the culvert’s capacity can be controlled by either the upstream and downstream flow conditions. The same culvert may change from one condition to another as the discharge through the culvert varies (Haestad, Dyhouse, 2003 p 233).